From data to decisions: introducing Knowledge Management to effect superior operations in a radiology department. (4th February 2008) - Goodfellow, T.; Bali, R.K.; Wickramasinghe, N.; Naguib, R.N.G.
Contemporary healthcare organisations have to develop an ability to intelligently use the knowledge assets already inherent within them as well as incorporate the new data and information they create daily. To do this effectively, superior tools and methods are required while Knowledge Management (KM) presents itself as an ideal enabler for transforming data to sound decisions. KM is based on a paradigm shift in the business environment where knowledge is central to organisational performance and, by way of effective clinical knowledge discovery techniques, can be used as a process that solves organisational problems by analysing data to identify patterns and relationships that can explain and predict behaviour. This paper examines the efficacy of KM for effecting superior operations in a real-life Clinical Radiology Department in the UK.